Economy-wide implications of energy build plans: A linked modeling approach - Arndt, Channing; Davies, Rob; Makrelov, Konstantin; Merven, Bruno; Hartley, Faaiqa; Thurlow, James (Elsevier, 2014)
We introduce a linked modeling framework based on existing computable general equilibrium and energy planning models for South Africa. The combined model provides for a more accurate assessment of the macroeconomic impacts of detailed energy build plans as it takes behavior changes into account. We apply the framework to alternative standard energy policies. We find that nuclear build plans constitute a significant risk to growth, particularly if cost overruns are experienced. Current results point to more detailed analysis of regional energy and renewable energy options, particularly if limiting carbon emissions is an objective.